Leksikon Peralatan Masak Tradisional Penganan Khas Masyarakat Lease, Kabupaten Maluku Tengah - Aipassa, Sulistiawati (Linguistik : Jurnal Bahasa dan Sastra, 2025)
The purpose of this study is to describe the transformation of lexicon and worldview surrounding traditional cooking utensils used for food preparation by the communities of Lease Island, Central Maluku Regency. The data consists of lexicons related to traditional cooking tools that have undergone transformation in the Lease Island communities—specifically in the villages of Tuhaha, Ihamahu, and Ouw—collected through interviews, observation, and literature review. The findings reveal a shift in the lexicon of traditional cooking utensils from Ambonese Malay to Indonesian and foreign languages. The study classifies the lexicon of traditional cooking utensils into two word classes: nouns and verbs, grouped as follows: (1) Traditional earthenware cooking utensils in Ouw Village – 51 lexicons (2) Traditional cooking utensils for sago and palm sugar-based dishes in Tuhaha Village – 33 lexicons (3) Traditional cooking utensils for Bagea, Sarut, and Sarut dishes in Ihamahu Village – 10 lexicons (4) Household utensils – 29 lexicons Conservation efforts for the traditional cooking lexicon of the Lease community in the G.Z. era include: (1) Documenting traditional cooking utensils through images, replicas, and promotion via social media (2) Reintroducing and encouraging the use of these lexicons in daily speech while maintaining awareness of their Indonesian equivalents